Effect of the crosslinking agent on porous networks formation of hema-based copolymers - Gomez, Cesar Gerardo (2004)
New copolymers of ethylene glycol dimethacrylate/2-hydroxyethyl methacrylate [poly(EGDMA-co-HEMA)],2,2′,2″-nitrilotriethyl triacrylate/2-hydroxyethyl methacrylate [poly(NTETA-co-HEMA)] and pentaerythritol tetraacrylate/2-hydroxyethyl methacrylate [poly(PETA-co-HEMA)] were obtained by suspension polymerization at 70 or 85 °C, using cyclohexane (Cyc) as porogen. In this work, the influence of the crosslinking agent (di, tri, or tetravinyl monomer) on the morphology of the polymeric networks was investigated. Swelling studies, Fourier Transform Infrared (FTIR) and mercury intrusion porosimetry, demonstrated that when both the vinyl groups number and molecular chain length between double bonds of the crosslinking agent decreased, networks with high porosity and crosslinking degree were generated.